Aktivitas Antibakteri Kombinasi Ekstrak Etanol Daun Kumis Kucing (Orthosiphon aristatus) dan Daun Mangga Madu (Mangifera indica L.) terhadap Propionibacterium acnes - Agus Kristina; Suprianto; Debi Meilani; Andy Febriadi; Shofian Syarifuddin (Jurnal Indah Sains dan Klinis, 2025)
Background: Acne is strongly linked to the overgrowth of Propionibacterium acnes. Because long-term use of conventional antibacterials may contribute to resistance and irritation, plant-derived extracts are being explored as alternative or complementary options. Kumis Kucing (Orthosiphon aristatus) and Mangga Madu (Mangifera indica L.) leaves are known to contain secondary metabolites that may help suppress bacterial growth. Objective: This study aimed to evaluate the antibacterial effect of combined ethanol extracts of O. aristatus and M. indica leaves against C. acnes and to determine which formulation ratio produced the best inhibition. Method: Each plant material was extracted separately using ethanol, then blended into five different combination formulas (F1–F5). Antibacterial activity was assessed in vitro using the disc diffusion technique with a standardized inoculum (0.5 McFarland). The diameter of the clear zone around each disc was measured and used to categorize antibacterial strength. Results: Qualitative phytochemical screening confirmed that both extracts contained key metabolite groups, including alkaloids, tannins/phenolics, flavonoids, and saponins. The negative control showed no clear zone, while clindamycin (positive control) produced a strong inhibition zone of 19.2 mm. All combined formulas inhibited C. acnes, with inhibition zones between 8.6 mm and 11.5 mm. Formula 3 generated the widest zone (11.5 mm; strong category), whereas Formula 2 showed the smallest inhibition (8.6 mm; weak category). Conclusion: The ethanol extracts of O. aristatus and M. indica leaves, when combined, were able to inhibit C. acnes. The level of inhibition varied with the mixing ratio, and Formula 3 demonstrated the most promising antibacterial activity among the tested formulations